Genetic dissection of assortative mating behavior - Merrill, Richard M.; Rastas, Pasi; Martin, Simon H.; Melo, Maria C.; Barker, Sarah; Davey, John; McMillan, W. Owen; Jiggins, Chris D. (PLOS Biology, 2019)
Author summary Many closely related animal species remain separate not because they fail to produce viable offspring but because they do not mate in the first place. When populations remain in contact, the evolution of behavioral barriers can be counteracted by ongoing hybridization that would homogenize differences between species. Hybridization could break down associations between genes underlying particular ecological adaptations and genes that cause individuals to mate with individuals that are similarly adapted. We studied two closely related species of tropical butterflies that differ in their wing patterns (white versus red), which are used both as warning signals and as mate recognition cues. By measuring preference behaviors in hybrids, we identified just three regions of the genome that explain a large proportion of the difference in behavior between these two species. One of these genetic regions is physically very close on the chromosome to a gene known to cause the red/white switch between these butterflies. By impeding the homogenizing effects of hybridization, the close association of these two loci may facilitate the evolution of behavioral barriers and, therefore, speciation despite ongoing gene flow.